Developing Video-Based Learning Media Through Role Play Strategy in Teaching Speaking of Recount Text - Wardatul Halwah; Alimin (PROJECT (Professional Journal of English Education), 2026)
This research focuses on the development of video-based learning media through role-play strategies in teaching speaking of recount text for the tenth graders. This research was carried out to address students' problem in speaking skills by developing appropriate, interesting, and contextual learning media based on the curriculum and the needs of teachers and students. This research used the Research and Development (R&D) method with the ADDIE model, which consists of five stages, there were analysis, design, development, implementation, and evaluation. The subjects of this research were an English teacher and tenth graders at SMA ASSA'ADAH Bungah. The data collection instruments used in the needs analysis stage included questionnaires and interviews. In addition, the instruments used in the evaluation stage included questionnaires for students and teacher to respond the developed media, observation sheets, and field notes. All data obtained were analyzed descriptively. The final product of this research is video-based learning media in MP4 format with a duration of 8 minutes and 10 seconds. The media was developed based on the Merdeka Curriculum and student needs. This learning video encourages active student participation, increases confidence in speaking, and creates a more interactive learning atmosphere.